(3GdJQNjU deRGhdI egfI GdJYdje aj eUQ aj VhA GdeYGjjQ GdYGdejI (B/s Remainder of title - (3,eUWaj eMehO CMeO eMeOs; (3fSQjf eMeO YHO GdZfj GdSjOs; (3EHQGgje GdOShbj YhV Gddgs (2023)
(3gOaJ GdOQGSI GdMGdjg Edi JbOje JUhQ ebJQM GdJQNjU deRGhdI egfI GdJYdje aj eUQ aj VhA GdeYGjjQ GdYGdejI(B.(3ef GLd VeGf GNJjGQ CaVd GdYGfGUQ hMeGjI GdegfI ef GdYfGUQ eJOfjI GdcaGAGJ GdGcGOjejI hGdegfjI(B, (3hPdc ai EWGQ OQGSI TGedI JJfGhd GdJCUjd hGdJMdjd GdJGQjNj hGdadSai dbVjI GdJQNjU deRGhdI egfI GdJYdje(B, (3dHYV GdJLGQH hGdNHQGJ GdGbdjejI hGdYGdejI ai gPG GdeLGd(B, (3hbO GSJNOeJ GdOQGSI GdefgL GdhUaj(B, (3hNdUJ Gdi JbOje JUhQ ebJQM dJWhjQ YedjI GdJQNjU deRGhdI egfI GdJYdje ai eUQ(B, (3eJVefkG adSaI hefWdbGJ hCgOGa hGdjGJ JWHjb(B, (3hcPdc VhGHW hJhUjGJ jfHZj eQGYGJgG dfLGM GdJWHjb CKfGA YQV GdJUhQ GdebJQM(B. (3jJeKd GdgOa GdQFjS ddOQGSI GdMGdjI aj GdJhUd Edi JUhQ ebJQM ddJQNjU deRGhdI egfI GdJYdje aj eUQ aj VhA HYV GdJLGQH GdEbdjejI hGdYGdejI GdeYGUQI hjfHKb efgG GdCgOGa GdJGdjI(B.(3GSJLdGA eaghe hadSaI GdJQNjU deRGhdI GdegfI (B-(3HUaI YGeI (B- (3hGdJYdje HUaI NGUI(B.(3JMOjO GdGSS hGdeHGOiA dJQNjU eRGhdI egfI GdJYdje(B, (3hGdeYJeOI YGdejkG ai eLGd GdJQNjU degfI GdJYdje HGdGSJaGOI ef NHQGJ GdOhd GdeJbOeI (B. (3GdJYQa hYQV hGbY eRGhdI egfI GdJYdje aj eUQ(B.(3YQV CHQR GdJLGQH GdEbdjejI hGdYGdejI GdeYGUQI aj eLGd GdJQNjU deRGhdI egfI GdJYdje efP GddHfGJ GdChdj(B. (3hVY JUhQ ebJQM dGLQGAGJ JWHjb GdJQNjU degfI GdJYdje ai eUQ ai VhA GdeYGjjQ GdYGdejI(B. s
The current study aimed to provide a proposal for icensing to practice the teaching profession in Egypt in the light of international standards, in order to ensure the selection of the best elements and protect the profession from elements of low academic and professional competence, within the framework of a comprehensive study dealing with the rooting and historical and philosophical analysis of the issue of licensing to practice the teaching profession, and insightful reading For some regional and global experiences and expertise in this field, the study used the descriptive approach, and concluded with presenting a suggested vision for developing the licensing process to practice the teaching profession in Egypt, including a philosophy, principles, objectives, and application mechanisms, as well as controls and recommendations that should be taken into account for the success of the application. A group of education experts to control and support it and ensure its sincerity and consistency of its items and themes.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2023. s
(3HHdjhLQGajG(B: (3UaMGJ (B135-147.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdJYdjes -- (3WQb GdJOQjSs; (3GdeOQShfs -- (3JOQjHs; (3GdJQNjU deRGhdI egfI GdJYdje aj eUQs -- (3GdeYGjjQ GdYGdejIs